2003
DOI: 10.1073/pnas.0306981100
|View full text |Cite
|
Sign up to set email alerts
|

Activation of peroxisome proliferator-activated receptor δ induces fatty acid β-oxidation in skeletal muscle and attenuates metabolic syndrome

Abstract: In this study, we defined the role of peroxisome proliferator-activated receptor ␤͞␦ (PPAR␦) in metabolic homeostasis by using subtype selective agonists. Analysis of rat L6 myotubes treated with the PPAR␦ subtype-selective agonist, GW501516, by the Affymetrix oligonucleotide microarrays revealed that PPAR␦ controls fatty acid oxidation by regulating genes involved in fatty acid transport, ␤-oxidation, and mitochondrial respiration. Similar PPAR␦-mediated gene activation was observed in the skeletal muscle of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

57
672
8
14

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 779 publications
(751 citation statements)
references
References 20 publications
57
672
8
14
Order By: Relevance
“…PPARd, the predominant PPAR isoform in skeletal muscle, is co-activated by PGC-1a (Wang et al 2003). Much like PGC-1a, PPARd regulates fatty acid oxidation via the transcription of genes involved in b-oxidation and energy uncoupling (Tanaka et al 2003;Wang et al 2003). In addition, PPARd is involved in regulating bone turnover (Scholtysek et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…PPARd, the predominant PPAR isoform in skeletal muscle, is co-activated by PGC-1a (Wang et al 2003). Much like PGC-1a, PPARd regulates fatty acid oxidation via the transcription of genes involved in b-oxidation and energy uncoupling (Tanaka et al 2003;Wang et al 2003). In addition, PPARd is involved in regulating bone turnover (Scholtysek et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…6, 7 The fatty acid utilization in the skeletal muscle could be enhanced in À87C carriers through a greater activation by PPAR-delta of genes involved in long chain fatty acids b-oxidation. 8,10 Therefore, carriers of the À87C allele might be protected from deleterious effects of a highfat diet on the lipid metabolism in comparison to the general population. It has also been demonstrated by Oliver et al 7 that PPAR-delta increases cholesterol efflux from macrophage, fibroblast and intestinal cells, in part through an increase in the expression of the ABCA1 reverse cholesterol transporter.…”
Section: Discussionmentioning
confidence: 99%
“…5 It has been shown that PPAR-delta is involved in the regulation of genes participating in lipid and lipoprotein metabolism 6,7 as well as in adipose tissue and muscle fatty acid oxidation. [8][9][10] Its role in cellular response to inflammation is also well characterized. 11,12 As for PPARa and PPARg, fatty acids are natural ligands of PPARdelta.…”
Section: Introductionmentioning
confidence: 99%
“…Increased Ppard expression in adipose tissue in mice is associated with reduced adiposity and lower serum lipid levels [9,10]. In addition, activation of PPARδ by treatment with a synthetic agonist ameliorates diet-induced obesity and insulin resistance in mice [10] and improves circulating lipid profiles in both obese rhesus monkeys and db/db mice [11,12]. In line with the outcome of studies in rodents, expression profiling studies in humans have shown an increase in PPARD expression following endurance exercise [13,14].…”
Section: Introductionmentioning
confidence: 87%
“…Additionally, a recent study of genetically modified mice provides evidence that PPARδ regulates glucose metabolism and insulin sensitivity in both skeletal muscle and the liver, interestingly indicating a subtle PPARδ-controlled change in substrate utilisation [8]. Increased Ppard expression in adipose tissue in mice is associated with reduced adiposity and lower serum lipid levels [9,10]. In addition, activation of PPARδ by treatment with a synthetic agonist ameliorates diet-induced obesity and insulin resistance in mice [10] and improves circulating lipid profiles in both obese rhesus monkeys and db/db mice [11,12].…”
Section: Introductionmentioning
confidence: 99%